2010
DOI: 10.1007/s10530-010-9910-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the alien algae Undaria pinnatifida (Phaeophyceae, Laminariales) on the diversity and abundance of benthic macrofauna in Golfo Nuevo (Patagonia, Argentina): potential implications for local food webs

Abstract: Changes in macroalgal community structure caused by invasive seaweeds have strong impacts on the associated macrofauna due to the role of macroalgae as autogenic ecosystem engineers. This study investigates the effect of Undaria pinnatifida on the abundance and diversity of benthic macrofauna in Golfo Nuevo, northern Patagonia, using a manipulative experiment involving the systematic removal of Undaria microthalli from strips of hard bottom during its eighth-month growing period. Species richness and diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 24 publications
1
45
0
4
Order By: Relevance
“…pinnatifida have been recorded in other invaded regions (Valentine and Johnson, 2005;Irigoyen et al, 2011;South et al, 2015). What is clear from our study is that, at the scale of sporophyte, U. pinnatifida harbours structurally distinct, less abundant and less diverse epibiotic assemblages than the longer-lived native kelps, L. ochroleuca and S. latissima.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…pinnatifida have been recorded in other invaded regions (Valentine and Johnson, 2005;Irigoyen et al, 2011;South et al, 2015). What is clear from our study is that, at the scale of sporophyte, U. pinnatifida harbours structurally distinct, less abundant and less diverse epibiotic assemblages than the longer-lived native kelps, L. ochroleuca and S. latissima.…”
Section: Discussionsupporting
confidence: 47%
“…Research into the effects of U. pinnatifida invasions on recipient macroalgae-dominated systems has shown varying impacts on local biodiversity. Studies have shown both an increase (Irigoyen et al, 2011) and a decrease (Curiel et al, 1998;Casas et al, 2004) in local diversity as a result of U. pinnatifida introductions, as well as subtle and inconsistent effects on native species and associated assemblages (Raffo et al, 2009;South et al, 2015). It is likely that U. pinnatifida impacts are context-dependent, but it does have the potential to affect the performance and/or abundance of native kelp species within Plymouth Sound because it is an opportunistic fast-growing species that occupies a substantial area of seabed by early summer (Heiser et al, 2014), and can shade co-existing native species (Smale, pers obs.).…”
Section: Introductionmentioning
confidence: 99%
“…habitat modification and changes in primary productivity) (Libralato et al, 2004;Okada et al, 2005), and climate change (Qui et al, 2010). In particular, studies demonstrate a positive relationship between kelp and decapod abundances (Johns and Mann, 1987;Daly and Konar, 2010;Irigoyen et al, 2011). In this study we make use of this relationship by employing decapod landing data as an indication of changes in kelp abundance, as no quantitative data on kelp abundance was present directly prior to the decline.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most invasive macroalgal species is the Japanese kelp Undaria pinnatifida (Harvey) Suringer, which has become established in the temperate zone worldwide (Silva et al 2002, Valentine & Johnson 2003, Edgar et al 2004, Farrell & Fletcher 2006, Martin & Cuevas 2006, Baez et al 2010, Irigoyen et al 2011). This seaweed arrived in New Zealand around 1987 and has since spread throughout much of the South Island (Hay & Villouta 1993, Parsons 1995, Stuart 2004, Russell et al 2008, aided by multiple incursions (Uwai et al 2006).…”
Section: Introductionmentioning
confidence: 99%